2021
DOI: 10.1001/jamaophthalmol.2020.6089
|View full text |Cite|
|
Sign up to set email alerts
|

Retinal Phenotype of Patients With Isolated Retinal Degeneration Due toCLN3Pathogenic Variants in a French Retinitis Pigmentosa Cohort

Abstract: IMPORTANCEBiallelic variants in CLN3 lead to a spectrum of diseases, ranging from severe neurodegeneration with retinal involvement (juvenile neuronal ceroid lipofuscinosis) to retina-restricted conditions. OBJECTIVE To provide a detailed description of the retinal phenotype of patients with isolated retinal degeneration harboring biallelic CLN3 pathogenic variants and to attempt a phenotype-genotype correlation associated with this gene defect. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 48 publications
3
38
0
Order By: Relevance
“…Also, the authors did not compare retinal findings among siblings in the 4 sibships in this report. 1 If the clinical course of the disease is consistent within pedigrees, this will give even more credence to their demonstration that the CLN3 pathogenic variants in these 2 groups of patients are associated with phenotypes that are milder than those of patients with classic juvenile NCL. Patients with classic juvenile NCL or Batten disease present with rapidly progressive loss of visual acuity followed by neurological deterioration in the first decade of life and demise as young adults.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Also, the authors did not compare retinal findings among siblings in the 4 sibships in this report. 1 If the clinical course of the disease is consistent within pedigrees, this will give even more credence to their demonstration that the CLN3 pathogenic variants in these 2 groups of patients are associated with phenotypes that are milder than those of patients with classic juvenile NCL. Patients with classic juvenile NCL or Batten disease present with rapidly progressive loss of visual acuity followed by neurological deterioration in the first decade of life and demise as young adults.…”
mentioning
confidence: 92%
“…6 Five of the 7 patients were reported to have mild neurological symptoms. While these authors provide more neurological details about their patients than Smirnov et al, 1 workup by neurologists who are experts in NCL and imaging studies with emphasis on more recently recognized changes attributable to CLN5 were not performed. 7 When a gene is expressed exclusively in the retina, its sequence variations will lead to isolated retinal disease.…”
mentioning
confidence: 99%
“… 1 The CLN3 gene is another good example wherein distinct biallelic variants can either cause a devastating and lethal condition, juvenile neuronal ceroid lipofuscinosis (Batten disease), or an isolated (non-syndromic) retinal degeneration (Smirnov et al, 2021; Mizobuchi et al, 2020; Chen et al, 2019; Ku et al, 2017). 2 , 3 , 4 , 5 …”
mentioning
confidence: 99%
“…Other non-syndromic forms include cone-rod dystrophies (OMIM 120970), Stargardt disease (OMIM 248200), X-linked retinoschisis (OMIM 312700) and many others. On the other hand, the most common syndromic form is Usher syndrome (USH) (OMIM 276900), a combination of hearing loss and RP (Castiglione and Moller, 2022).Although several genetic studies have identified novel IRDs-associated genes and genetic variations, most of these associations and gene prevalence data were based on cohorts in Western Europe and North America (Smirnov et al, 2021;Colombo et al, 2021). Although the genetic basis of IRDs varies among patient cohorts, even replication for the major findings is still lacking in understudied ethnicities (Jaffal et al, 2021).…”
mentioning
confidence: 99%
“…Although several genetic studies have identified novel IRDs-associated genes and genetic variations, most of these associations and gene prevalence data were based on cohorts in Western Europe and North America ( Smirnov et al, 2021 ; Colombo et al, 2021 ). Although the genetic basis of IRDs varies among patient cohorts, even replication for the major findings is still lacking in understudied ethnicities ( Jaffal et al, 2021 ).…”
mentioning
confidence: 99%